Bone age Assessment by Greulich and Pyle Method in Thai Children at Lamphun Hospital - Panmethis, Melissa; Sirapallop, Orawan; Tepprasong, Netnapa (Journal of Health Science of Thailand, 2017)
This cross-sectional study was aimed at determining whether the Greulich and Pyle method still capable of bone age assessment in Thai children at Lamphun hospital. The normal appearance left hand radiographs were enrolled from 106 Thai children (68 males, 38 females), aged 2 months to 19 years, visiting the emergency and outpatient departments during June 2005-August 2007. The radiographs were analyzed by two radiologists blinded to the chronological age. The mean age difference, their standard deviation and 95% CI were calculated. On average, there was no statistically difference between bone age reported by two radiologists and chronological ages (p 0.13 and p 0.68). However, delayed bone ages in boys aged 6-12 yrs (-0.90 yr, p < 0.01 and -0.85 yr, p< 0.01) and advanced bone ages in boys aged 12-19 yrs (0.50 yr p < 0.01 and 0.44 yr, p 0.02) were found. In girls, although the results between measured bone ages and chronological ages from the two readers were not different in 1-12 yr age group, but the difference were statistically significant for only one radiologist in 1-3 yr group (0.60 yr, p 0.04) and 3-6 yr (-0.78 yr, p 0.02 ). The rest of the girls, statistical significance of advanced bone age was found only in one radiologist in 12-19 yr age group (0.94 yr, p 0.01). The data suggested the discrepancy between measured bone age and chronological age in some age groups, therefore, some modification of Greulich and Pyle method or identified the new standard bone age for Thai children is necessary.